TEACHER’S FEEDBACK ON WRITING RECOUNT TEXT ON THE GRADE EIGHT STUDENTS OF MTS TARBIYAH ISLAMIYAH HAJORAN - Rizki Indah Sari Hasibuan; Yeni Erlita (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2021)
The objective of the study were investigate the types of teacher’s feedback on writing which given by the teacher’s and to find out how the teacher’s gave feedback on writing recount text on the grade eight, to elaborate the reasons of the teacher conducting the feedback on students writing of grade eight in MTs Tarbiyah Islamiyah Hajoran. This research used descriptive qualitative method and the data were collected through documentation and interview. The data was analyzed in four steps: 1). Data Collection, 2) Data Condensation, 3) Data Display, 4) Conclusion and Drawing/ verifying. The findings There were two types of feedback found on students’ writing recount text on the grade eight students of MTs Tarbiyah Islamiyah Hajoran. They were : Direct and Indirect. First the teacher gave direct feedback by giving some signs to indicate their error words such as circle,line and crosswise then provide the corect form directly. The teacher also added the letters or words to make the clear sentence. Direct feedback which is provided in the 37 of the total feedback and has perecentage as many as 79%. Second , it was indirect feedback, the indicated the students error exists without gave the correct form. It has many percentages 21% of 10 the total feedback. Based on the analysis interview, the reason why the teacher used those types of feedback on students’ writing was because it could make the students’ have more vocabularies and the students did not think more about what was the correct word. In conclusion, teacher’s feedback are important to make student aware of making mistake on their writing task. The finding suggested that the English teacher should give the written feedback to students’ writing task to enable the improve the writing skill.Keywords: Teachers’ feedback, Students, Recount Text, Writing